Ibn Hamids al-Siqilli is an ascetic (Journal of the College of Basic Education, 2022)
Asceticism is means to achieve high morality and perfection by triumphing over the soul, conquering its passions, suppressing its desires, resorting only to Allah and leaving worldly pleasures. Asceticism is an important and popular topic in Arab literature; therefore, this study has been conducted to shed light on the factors and causes of its popularity in Andalusia and the extent of its effect on Andalusia literature, making the poet, Ibn Hamad Yasin All- Siqli, its domain .So, the study is entitled'' Ibn Hamad Yasin All-Siqli as an ascetic'' . It has reached several findings including that Ibn Hamad Yasin's asceticism was not developed out of faith he adhered to or a line he set for himself, but it is a normal situation occurred to those reckless person when they grow old and become closer to the edge of grave . It also shows that the incentives and reasons of asceticism are numerous and are not restricted to the religious motives and Islamic tradition. Thus, it demonstrates that his poetry was colored according to the junctures of his life and the incidents he had come through.